Peran Guru Dalam Mengatasi Kenakalan Siswa Kelas IV SD Negeri 0506 Tangga Bosi - Daulay, Irma Sari; Hasibuan, Juhriyah; Harahap, Nurhalimah (Journal Education Innovation (JEI), 2025)
The purpose of this study was to determine: (1) forms of delinquency of class IV students of SD Negeri 0506 Tangga Bosi. (2) factors that cause delinquency of class IV students of SD Negeri 0506 Tangga Bosi.  (3) how the teacher overcomes the delinquency of class IV students of SD Negeri 0506 Tangga Bosi. This research uses a type of qualitative research, namely research that produces data in the form of written or spoken words from the people observed. There are two data sources that researchers use, namely primary data sources and secondary data sources. Primary data sources are data directly taken from the object of research, namely students and class IV teachers. This primary data source comes from field data obtained from observations and interviews. Secondary data sources are data taken in the form of documents, such as books, books, dictionaries and other literature related to overcoming student delinquency. Researchers checked the validity of the data by triangulating sources and triangulating techniques. The forms of delinquency that exist in class IV of SD Negeri 0506 Tangga Bosi are: 1) being late for school, 2) rarely doing assignments, 3) skipping class, 4) fighting, 5) nosy, 6) ignorant, 7) often disturbing his friend while studying, 8) oversleeping, 9) lazy, 10) cheating. The causative factors that influence student delinquency in class IV SD Negeri 0506 Tangga Bosi are family factors, such as lack of attention and affection from the family with mediocre economic conditions so that the child's wishes are not fulfilled, parents who are broken home so that it causes the child's mentality to be disturbed so that at home only with his grandmother and grandfather. Furthermore, community environmental factors, in this society there is promiscuity and supervision from parents is lacking so that children can freely make friends with anyone without knowing their background and the advancement of technology so that children can just access whatever they want, school environmental factors in the school environment student conditions are also less supportive, for example from their friends when their friends tell them something and the child does not do it, they will be underestimated and can even be antagonized by other friends. Classroom teacher efforts in dealing with student delinquency in class IV SD Negeri 0506 Tangga Bosi namely such as 1) personal approach, 2) strengthening positive discipline, 3) collaborative approach, 4) interesting learning methods, 5) providing guidance and coaching, 6) effective classroom management, 7) preventive approach by supervising handling such as providing understanding or initial guidance to students of SD Negeri 0506 Tangga Bosi.